(untitled) (Global Journal of Management and Business Research, 2022)
As human resources (HR) are considered a strategic capital and the success of an organization highly depends on skilled manpower, it is essential to investigate HR disclosure practices. Limited research on human resource disclosure from an accounting perspective in the developing country motivates this study. The study aims to evaluate the human resources disclosure practices in the Bangladeshi banking industry. Using content analysis, the disclosure data are collected from the annual reports of 30 listed banks on the Dhaka stock exchange (DSE). 40% of the sample banks disclose the HR practices within the range of 50%-60%, indicating that the banking sector has a wide scope to improve its HR practices. The average HR disclosure practice in the banking industry in Bangladesh is 59.25%. Of which, the highest disclosure is recorded by the HR development 91.25%, while the lowest is in the health and safety, documented by only 19.45%. the highest HR practices are recorded by Prime bank ltd. Therefore, the study suggests the banks#x2019; managers, regulatory bodies and academicians focus more on the HR disclosure issue to encourage more disclosure of information related to human resources and formulate relevant policies that might create a more favorable working environment for the HR.